The Madonna of the Magnificat. - Stone, George Eathl (photographer):::Creator::::::::::::
The image depicts a painting of the Virgin sitting with Child, in her right hand a quill; the youth to the right hold the book and the ink bottle. The books text on the verso, begins: "Magnificat aia mea Dnm" (Magnificat anima mea Dominum) - My soul doth magnify the Lord 1444/7 - 1510).